2021
DOI: 10.3390/su13158332
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Slope Gradient and Aspect on Soil Organic Carbon Content in the Region of Niš, Serbia

Abstract: Topography-induced microclimate differences determine the local spatial variation of soil characteristics as topographic factors may play the most essential role in changing the climatic pattern. The aim of this study was to investigate the spatial distribution of soil organic carbon (SOC) with respect to the slope gradient and aspect, and to quantify their influence on SOC within different land use/cover classes. The study area is the Region of Niš in Serbia, which is characterized by complex topography with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 43 publications
3
21
1
Order By: Relevance
“…This difference may be due to the depth of sampling, studies that sampled close to the surface have a higher correlation between NDVI and SOC. The influence of slope on SOC content is not significant, so our results are similar to the recent study mentioned (Jakšić et al, 2021). This may be due to the influence of farming practices.…”
Section: Discussionsupporting
confidence: 91%
“…This difference may be due to the depth of sampling, studies that sampled close to the surface have a higher correlation between NDVI and SOC. The influence of slope on SOC content is not significant, so our results are similar to the recent study mentioned (Jakšić et al, 2021). This may be due to the influence of farming practices.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, Ding et al [51] found that soils of alpine grasslands of the Tibetan Plateau (>4000 m) were also characterized by significant carbon accumulation from the 2000s to the 2010s. It was widely acknowledged that the increase in temperature could stimulate the activity of soil microorganisms, thus accelerating the loss rate of carbon from the soil into the atmosphere [20,52,53]. However, for high-elevation zones, the increase in temperature could also enhance the accumulated temperature, which prolongs the growing season and further stimulates the vegetation productivity.…”
Section: Elevation-dependent Soc Dynamicsmentioning
confidence: 99%
“…Currently, galvanized wire mesh and three‐dimensional (plastic) mesh are the most commonly used soil consolidation meshes, and their differences are bound to directly or indirectly affect biotic or/and abiotic factors, and then change soil properties of a cut slope. However, the current studies on cut slopes were based on galvanized wire mesh as the consolidation mesh (Huang et al, 2017; Li, Kan, et al, 2018; Li, Zhang, et al, 2018; Zhu et al, 2020; Jakšić et al, 2021; Jiang et al, 2021) and ignored the difference between three‐dimensional mesh and galvanized wire mesh. Additionally, there have been few comparative studies on the effect of treating a cut slope with three‐dimensional mesh and galvanized wire mesh on SOC stock changes.…”
Section: Introductionmentioning
confidence: 99%